Relationship Between Fatigue, Cognitive Functions, Depression, and Disability in Multiple Sclerosis Patients - Gökçe Zeytin Demiral (Acta Medica Alanya)
Aim : Multiple Sclerosis (MS) is a chronic, progressive, and neurodegenerative disorder of the central nervous system. It frequently leads to symptoms such as disability, cognitive impairment, fatigue, and depression. This study aims to examine the relationship between fatigue, cognitive functions, depression, and disability among individuals with MS.Methods: Seventy-four MS patients were evaluated by using the Cognitive Failure Questionnaire (CFQ) battery. The Expanded Disability Status Scale (EDSS) was used in determining the level of disability, whereas the Fatigue Severity Scale (FSS) and the Beck Depression Inventory (BDI) were utilized in measuring the levels of fatigue and depression, respectively.Results :Moderate positive correlations were found between EDSS and BDI (r1=0.342; p<0.001), between EDSS and FSS (r1=0.392; p<0.001), between CFQ and BDI (r1=0.451; p<0.001), between CFQ and FSS (r1=0.425; p<0.001), and between FSS and BDI (r1=0.424; p<0.001).Conclusion :The results achieved in this study indicate that fatigue and depression increase as disability increases among Multiple Sclerosis patients and cognitive impairment is associated with both depression and fatigue.